Collaborative governance in green tourism village administration in Bali through SIDeWi*HuB - Deddy Kurniawan Halim; Susanti Susanti; Faizal Madya; Ni Putu Tirka Widanti (Department of Government Studies, Universitas Muhammadiyah Makassar, 2025)
This study examines collaborative governance in Bali’s Green Tourism Villages (Desa Wisata Hijau, DWH) as a strategy for post–COVID-19 rural tourism sustainability amid urban hotel oversupply and environmental degradation. A mixed-methods design was employed, combining quantitative survey data from 126 respondents across 28 tourism villages with qualitative–secondary analysis of policy documents, tourism statistics, and environmental reports to contextualize empirical findings beyond the village level. Quantitative data were collected through the SIDeWiHuB digital platform, which integrates sustainability assessment, village registration, and DeWiKu e-commerce services. Three constructs were measured using validated multi-item scales: Need for Green Village (N-GreenV), Community Participation (CP), and Perception of Sustainability (PS), derived from established sustainability and participatory tourism frameworks and benchmarked against normative standards developed from prior baseline studies. Internal consistency and construct validity were assessed before analysis. Multiple linear regression was applied, with diagnostic checks for normality, multicollinearity, and model fit conducted to ensure robustness. Results indicate that all sampled villages met the Kalpataru 5 (greenest) classification threshold. This findings demonstrate the analytical validity of SIDeWiHuB as a digitally enabled collaborative governance instrument within a Pentahelix framework and support its potential scalability as a policy tool for sustainable rural tourism governance in Indonesia.